FORWARD MODELLING METODE GAYABERAT DENGAN MODEL INTRUSI DAN PATAHAN MENGGUNAKAN OCTAVE - Muhammad Nurul; Syamsurijal Rasimeng; Ida Bagus Suananda Yogi; Aprillia Yulianata; Aisah Yuliantina (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2020)
The gravity method is a geophysical exploration method to measure variations in the acceleration of gravity on the surface of the earth in response to variations in rocks that exist beneath the surface. In gravity exploration requires a preliminary picture as a reference for measurement. This study aims to make forward modeling synthetic OCTAVE based using synthetic data on subsurface rock structures, so as to produce intrusion and fracture models based on differences in the value of the acceleration of gravity from one point to another on the surface of the earth. Synthetic modeling with the geological parameter approach of the study area is based on variations in the price of rock density. The model parameters used in intrusion modeling are the density value of 2.7 g/cm3 and the depth of 850 meters while the fracture modeling uses a density value of 2.7 g/cm3 with a depth of 350 meters and 360 meters and a thickness of 500 meters. From intrusion modeling, the gravity vertical component of attraction force is 0.03 mGal and in the fracture modeling the gravity vertical component of attraction force is 0.0565 mGal. Based on the results of this modeling, distance curve vs. gravity anomaly response is obtained for both cases. In the intrusion rock model obtained by the profile model with an open type down. While the fracture modeling is obtained anomalous profile curve variation which states that in the fracture area with a significant change in the direction of the curve.